Genealogical Custodianship and Layered Authority: Heritage Governance at the Amangkurat I Tomb, Indonesia - Imania, Zikhra Dwi; Hakim, Lukmanul; Susanto, Dedy (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
Religious tourism governance becomes complex when ritual authority, heritage administration, tourism planning, devotional recognition, and local livelihoods overlap. Existing studies emphasize collaboration and service improvement but provide limited explanations of how formal coordination can be introduced at sites where genealogical custodianship constitutes part of the governance structure. This study examines how sacred authority, genealogical custodianship, and cultural-heritage governance shape the management of the Amangkurat I Tomb; identifies the associated power relations and institutional problems; and formulates a context-sensitive institutional initiation strategy. A qualitative case study was conducted in January 2026 with 21 purposively selected informants comprising a key custodian, repeat pilgrims, nearby residents, local traders, and government officials. Data from interviews, non-participant observation, and documentary sources were examined through coding, triangulation, and interpretive comparison. The findings show that the authority of the abdi dalem derives from genealogical succession, reported court appointment, ritual service, and recognition by pilgrims. This authority coexists with cultural-heritage regulation, tourism planning, community interests, and local livelihoods, but these domains are not connected through a documented cross-actor mechanism. The resulting problems include concentrated custodial workloads, incomplete visitor records, pressure on facilities during peak periods, contested historical narratives, limited community consultation, and concerns about the position of local traders. The study formulates a six-stage institutional initiation strategy beginning with authority mapping and a limited coordination forum before administrative, legal, promotional, or physical development. This strategy is an analytical proposal rather than an implemented model. The study contributes a layered-authority perspective in which institutional development connects, rather than replaces, genealogical and ritual custodianship.